2023
DOI: 10.3390/ijms241411598
|View full text |Cite
|
Sign up to set email alerts
|

NFE2L2 and STAT3 Converge on Common Targets to Promote Survival of Primary Lymphoma Cells

Abstract: NFE2L2 and STAT3 are key pro-survival molecules, and thus, their targeting may represent a promising anti-cancer strategy. In this study, we found that a positive feedback loop occurred between them and provided evidence that their concomitant inhibition efficiently impaired the survival of PEL cells, a rare, aggressive B cell lymphoma associated with the gammaherpesvirus KSHV and often also EBV. At the molecular level, we found that NFE2L2 and STAT3 converged in the regulation of several pro-survival molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown that the inhibition of STAT3 Y705 tyrosine phosphorylation, mainly mediated by Janus activating kinases (JAK) 2, may be an effective strategy for reducing the survival of PEL cells [ 5 , 6 ]. Notably, STAT3 engages in crosstalk with other pro-survival pathways, e.g., nuclear factor erythroid 2–related factor 2 (NRF2) [ 7 ] and mutant p53 [ 8 , 9 ], to further promote tumorigenesis; on the other hand, it may negatively influence the activation of wtp53 in PEL cells [ 10 ]. Other than phosphorylation, STAT3 may undergo other post-translational modifications that affect its activity, and among those, it may be acetylated [ 11 ] or methylated [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the inhibition of STAT3 Y705 tyrosine phosphorylation, mainly mediated by Janus activating kinases (JAK) 2, may be an effective strategy for reducing the survival of PEL cells [ 5 , 6 ]. Notably, STAT3 engages in crosstalk with other pro-survival pathways, e.g., nuclear factor erythroid 2–related factor 2 (NRF2) [ 7 ] and mutant p53 [ 8 , 9 ], to further promote tumorigenesis; on the other hand, it may negatively influence the activation of wtp53 in PEL cells [ 10 ]. Other than phosphorylation, STAT3 may undergo other post-translational modifications that affect its activity, and among those, it may be acetylated [ 11 ] or methylated [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%